TEACHING ENGLISH FOR YOUNG LEARNERS IN RURAL AREA: TEACHERS’ CHALLENGES - Buyun Khulel (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
Rural education, in comparison to its urban and suburban counterparts, is seen to face a distinct challenge. The location and implementation of an English curriculum in primary school are significant problems. As a result, the purpose of this study is to look into the difficulties that English teachers face when teaching English to young learners in rural public primary schools in Baureno, East Java. A semi-structured interview with six participants from six elementary schools in five villages (Gajah, Gunungsari, Tulungagung, Selorejo, and Blongsong) is utilized to address the question. It begins by briefly reviewing the role of English in the national primary school curriculum on the one hand, and the implementation of English programs in rural schools on the other. Throughout the research, the researcher encountered three difficulties: (i) Students’ socio-economics condition, (ii) the status of English in the school, and (iii) Covid-19 pandemic. As a result, the writer suggested that more research be done to highlight English teachers’challenges on the implementation of primary school learning. The findings of the study can be used by English teachers, stakeholders, policymakers, and institutions to develop practical strategies for teaching English in primary school.